2010
DOI: 10.1177/0898264310366737
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Perceived Effectiveness of Local Long-Term Care Ombudsman Programs in New York and California

Abstract: Findings highlight variability within and between the local LTCOPs in California and New York.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
3
0
2
Order By: Relevance
“…L'Ombudsman est directement concerné par une démarche évaluative qui lui permet de mesurer sa performance afin d'améliorer ses services. De leur côté, les autorités gouvernementales et législatives constituent également des acteurs clefs, car, non seulement, elles s'intéressent à sa gestion, mais elles souhaitent aussi connaître ses impacts sur l'administration publique en particulier et sur la société en général (Aufrecht et Hertogh, 2000;Danet, 1978;Fortier, 2009;Mohammed, 1991;Stuhmcke, 2012). Les administrations publiques contre lesquelles les plaintes des usagers sont dirigées s'intéressent elles aussi à l' évaluation de l'Ombudsman.…”
Section: Discussion : Des Défis Et Des Enjeux à L'évaluation De La Peunclassified
See 1 more Smart Citation
“…L'Ombudsman est directement concerné par une démarche évaluative qui lui permet de mesurer sa performance afin d'améliorer ses services. De leur côté, les autorités gouvernementales et législatives constituent également des acteurs clefs, car, non seulement, elles s'intéressent à sa gestion, mais elles souhaitent aussi connaître ses impacts sur l'administration publique en particulier et sur la société en général (Aufrecht et Hertogh, 2000;Danet, 1978;Fortier, 2009;Mohammed, 1991;Stuhmcke, 2012). Les administrations publiques contre lesquelles les plaintes des usagers sont dirigées s'intéressent elles aussi à l' évaluation de l'Ombudsman.…”
Section: Discussion : Des Défis Et Des Enjeux à L'évaluation De La Peunclassified
“…L'une des caractéristiques de ce modèle est qu'il s'appuie sur l' évolution du volume de plaintes traitées pour évaluer la dimension « clientèle ». Cependant, un volume important de plaintes ou une diminution du nombre de plaintes enregistrées ne sont pas des mesures suffisantes pour apprécier pleinement la performance de cette organisation (Fortier, 2009;Hannigan, 1977). En effet, une augmentation du volume de plaintes d'une année à l'autre peut refléter une augmentation des injustices administratives ou une amélioration de la notoriété ou de l'accessibilité à l'Ombudsman.…”
Section: Vers Une Congruence Des Modèles D'évaluation De L'ombudsmanunclassified
“…Effectiveness ratings were provided on 4-point Likert-type scales (0 = very ineffective to 3 = very effective ). Although not providing an absolute criterion of program performance, self-rated efficacy measures have been used in prior research efforts in this topic area (Estes et al, 2004; Estes et al, 2006; Estes et al, 2007; Estes et al, 2010; Harris-Whehling et al, 1995; Hughes, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The IOM study identified insufficient resources as a factor associated with the effectiveness of state LTCOPs. This study was to be followed by a 50 state study funded by the Kaiser Family Foundation (KFF; Estes, Zulman, Goldberg, & Ogawa, 2004) and 4 separate statewide studies of LLTCOPs in California, New York (Estes, Goldberg, Lohrer, Nelson, & Hollister, 2006; Estes et al, 2010), Illinois (Hughes, 2007), Ohio (Wellin & Kart, 2008 ), and Georgia (Estes, Hollister, & Goldberg, 2007). All of the aforementioned studies, the IOM national study, the 50 state KFF funded study, and the 5 individual state studies’ (funded by private foundations and public funds) illustrate the continued interest of those concerned with long-term care policy in evaluating and strengthening the LTCOP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation